Topical Antibiotic Optimization of Wijayakusuma Plant (Epiphyllum oxypetalum) as Mosquito Repellent Therapy Oil - Agus Darwanto, Agus Darwanto; Rindi, Kis Rindiana Subroto; Novita, Novita Dian Susilowati (International Journal of Health Literacy and Science, 2023)
Wijayakusuma plants contain various active compounds that are beneficial to health, such as alkaloids, triterpenoids, and saponins. This research aims to optimize topical antibiotic products from Wijayakusuma plant that were synergized with Sambung Nyawa, Sambang Darah, Bratawali, Sambilata, and Tobacco leaves into a therapeutic oil for a mosquito repellent. The topical antibiotics were made by maceration method by soaking wijayakusuma, sambung nyawa, sambilata, bratawali, sambang getih, and tobacco leaves using VCO then tested by viscosity test, antibacterial test, phytochemical screening, antioxidant test, and efficacy test. Data were analyzed with descriptive statistics. The results showed that viscosity measurement with Oswald 20oC showed 22.56 cP. Antioxidant analysis used the % DPPH inhibition method with a sample of 50,000 ppm was 51.6%. Antibacterial activity against Bacillus subtilis (grampositive) was 18.8 mm (strong), and against Escherichia coli (gram-negative) was 10.4 mm (strong). The equivalent flavonoids as topical antibiotics contained 15.51 mg QE/ml, phenolics 8.11 mg GAE/ml, and tannins 11.30 mg TAE/ml. Mosquitoes stumbled and flew away when exposed to this topical antibiotic. This topical antibiotic has good antioxidant content for body care, antibacterial and aromatherapy that repels mosquitoes, and is suitable for external massage oil treatment.